KEMAMPUAN PROSES SAINS SISWA MELALUI PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN IPA TERPADU PADA TEMA GLOBAL WARMING - Pramita Sylvia Dewi (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2016)
Abstract The purpose of this study was to implement an integrated science learning in order to reveal student’s scientific process skills. Subjects of this study were Grade VII students of SMP in Bandar Lampung. This study used a quantitative approach. Data was collected using test and video recording. With regards to the implementation of the integrated science learning, the data showed that such learning approach has been relatively well implemented. This contributed to the data of students’ scientific process skills which was observed to be improved by 7.5%. This result was strengthened by the data from video recording that showed an adequate achievement of scientific skills indicators. The average percentage of scientific indicators of explaining scientific phenomena, evaluating and designing scientific in research, and interpreting the data and scientific avidence were respectively 68,6%, 77,1%, and 81,7%. These values indicated an overall improvement of 11,5% that was considered to be good. More importantly, students and teachers showed positive response on the integrated science learning. Abstrak Tujuan penelitian ini adalah menerapkan pembelajaran IPA Terpadu untuk mengungkap kemampuan proses sains siswa. Subjek penelitian adalah siswa kelas VII di SMP Negeri Kota Bandar Lampung. Penelitian menggunakan pendekatan kuantitaif. Data dikumpulkan menggunakan soal tes dan perekaman video. Berkaitan dengan penerapan IPA terpadu, data menunjukkan bahwa pembelajaran tersebut telah dilaksanakan dengan relatif baik. Hal ini berdampak pada data kemampuan proses sains siswa yang terlihat meningkat sebanyak 7.5%. Hasil ini diperkuat dengan data dari rekaman video yang menunjukkan pencapaian yang cukup baik pada indikator-indikator kemampuan saintifik. Rata-rata persentase dari indikator saintifik fenomena, mengevaluasi dan merancang penelitian, dan menginterpretasi data dan bukti ilmiah adalah masing-masing 68,6%, 77,1%, and 81,7%. Nilai tersebut mengindikasikan peningkatan keseluruhan sebanyak 11.5% yang cenderung baik. Lebih penting, para siswa dan guru menunjukkan tanggapan positif pada pembelajaran IPA Terpadu. Permalink/DOI: http://dx.doi.org/10.15408/es.v8i1.1564